Causes and Effects of Land Degradation in Karangazi Sector, Nyagatare District Rwanda. - Fred, Mujyambere (Kabale University, 2019)
A Research Report Submitted to the Faculty of Science in Partial Fulfillment of the Requirement For the Award of a Degree of Bachelor of Land Use Planning and Management of Kabale University.